(untitled) (American Journal of Management, 2023)
The 2008 recession caused unemployment, motivating individuals to evaluate their work-related identity. We qualitatively study such identity transitions and emotions during: (1) involuntary job loss, (2) subsequent unemployment, (3) job search, (4) underemployment, and (5) reemployment. We analyzed fifteen blogs of individuals laid off from October 2008 to April 2011. Blogs provide a rich medium to study of thoughts and feelings due to non-researcher-influenced discourse. Using grounded theory, we construct a model of the various transitions work-related identity undergoes. We also note how opposing sets of emotions interact with cognitive ideological techniques during identity transitions to produce varying outcomes.